Risk-Averse by Nation or by Religion? Some Insights on the Determinants of Individual Risk Attitudes - Stephan Bartke; Reimund Schwarze (Deutsches Institut für Wirtschaftsforschung (DIW), 2008)
Research findings have proven that the willingness to take risks is distributed heterogeneously among individuals. In the general public, there is a widely held notion that individuals of certain nationalities tend to hold certain typical risk preferences. Furthermore, religious beliefs are thought to explain differences in risk-preparedness on the individual level. We analyze these two possible determinants of individual risk attitudes: nationality and religion. First addressing the study of risk attitudes in a literature review, we then test our hypotheses empirically using the large, representative German Socio-Economic Panel (SOEP). To understand the importance of nationality, we focus on emigrants to Germany. The key findings are: (1) Nationality is not a valid determinant of risk attitudes. It can be broken down into several constituent factors including religion. (2) Religiousness is a significant determinant of risk attitudes. Religious persons are less risk-tolerant than atheists. Moreover, religious affiliation matters: Muslims are less risk-tolerant than Christians.
Keywords: D10; D80; D81; J15; Z12; 330; Risk Aversion; Nationality; Immigrants; Religion; Germany